Foreshadowing Overuse: A Stylistic Approach to Modernist Fictional Writing - Shuhaib, Mahdi (Al-Adab Journal, 2024)
As a descriptive study, this article examines the significance of stylistic analysis in observing fiction, focusing on the use of foreshadowing. The author investigates the potential overuse of foreshadowing in selected modern cultural novels and analyses its impact on the plot and the suspense of the readers. The study examines the use of foreshadowing to deconstruct the difficulty novelists face in crafting immaculate works. It concludes that foreshadowing is an integral part of any literary work, regardless of its type or genre, and that it cannot be restricted to particular words. Furthermore, the "tense" factor in most modern works is not fixed or regulated due to the overuse of the flashback technique. The discussion examines Mr. Dalloway by Virginia Woolf and A Portrait of the Artist as a Young Man by James Joyce. Mrs. Dalloway’s linguistic variables demonstrate that foreshadowing predominates the plot, as Woolf’s foreshadowing lexis continually alludes to Septimus and Clarissa’s plight. A Portrait of the Artist as a Young Man heavily uses concrete lexemes to foreshadow Daedalus’ evolution, whereas Mrs. Dalloway focuses on speech and abstract lexemes.